The representation of science and scientists on postage stamps : a science communication study - Yardley, Christopher B. (Australian National University, 2015)
"For approaching two centuries, the images on postage stamps have been used to convey messages from the government of the day to the general public. Science has been used to enhance those messages for the past nine decades. In this book, I explore the ways in which science and scientists have been portrayed on stamps and look at the ideas and, in some cases, the propaganda that underpins them."--Page 1